Discovery of Intra-Abdominal Hemorrhage during Hernioplasty in a Patient Taking Rivaroxaban - Harry Chow; Michael K. Ng (Case Reports in Surgery)
We discuss the first ever case of rivaroxaban causing major intra-abdominal hemorrhage found in a patient during emergency hernioplasty. The source of bleeding was not identified either intra- or postoperatively. This is on a background of treatment for deep vein thrombosis (DVT) with rivaroxaban, a complication that resulted from a total knee arthroplasty performed four weeks prior. Rivaroxaban is a new generation of anticoagulants that directly inhibits factor Xa and is used for DVT treatment in major orthopaedic surgery. Here we discuss the major side effects of rivaroxaban, namely, the increased risk of major bleeding as well as the irreversibility of this anticoagulant, should such bleeding occur. We advise caution in the use of rivaroxaban even in patients that are at low risk of bleeding given the discovery of hemorrhage as presented in this case.